Mangrove Vegetation Analysis and Zonation in Cemara Beach, Banyuwangi - Cahyadi, Ferry Dwi; Shabrina, Aafiyah Maryam Nur; Prasetiyo, Himawan; Puspitasari, Laksmi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Cemara Beach in Banyuwangi Regency has a unique mangrove ecosystem with a river flow that limits the tidal area with the land behind it. This study aims to determine the structure and composition of mangroves in Cemara Beach and its zoning. The method used is a vegetation survey with a transect plot. Data were analyzed using ecological indices and zoning illustrated from the results of vegetation surveys and observations. The results show that the Casuarina equisetifolia species has the highest important value index (IVI) in tree-level vegetation with an IVI value of 128.29%, while the highest IVI at the sapling level is owned by the Rhizophora mucronata species of 86.72% and the Acanthus ilicifolius species of 64.41% at the seedling level. The species diversity index (H') and dominance index (D) of mangroves in Cemara Beach are classified as moderate with average values ​​of 1.21 and 0.35. Then the species evenness index (E) of mangroves in Cemara Beach is included in the high category with an average E value approaching one at 0.78, while the species richness index (R) is classified as very low with an average value of 0.93. The zoning formed in mangrove vegetation in Cemara Beach is in sequence from sea to land, namely Casuarina equisetifolia, Rhizophora mucronata, Acanthus ilicifolius, Avicennia alba, Sonneratia alba, and Excoecaria agallocha. These findings suggest the need for targeted conservation and rehabilitation strategies that consider the natural zonation and dominance patterns of mangrove species to maintain the ecological balance of Cemara Beach.